Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1038/ncomms1646
|View full text |Cite
|
Sign up to set email alerts
|

Propagation stability of self-reconstructing Bessel beams enables contrast-enhanced imaging in thick media

Abstract: Laser beams that can self-reconstruct their initial beam profile even in the presence of massive phase perturbations are able to propagate deeper into inhomogeneous media. This ability has crucial advantages for light sheet-based microscopy in thick media, such as cell clusters, embryos, skin or brain tissue or plants, as well as scattering synthetic materials. A ring system around the central intensity maximum of a Bessel beam enables its self-reconstruction, but at the same time illuminates out-of-focus regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
206
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(206 citation statements)
references
References 19 publications
0
206
0
Order By: Relevance
“…Finally, alternative illumination schemes other than the Gaussian beams modeled within this study have also been reported in the literature (structured illumination, Bessel and Airy beams, multi-photon, etc.) [49][50][51][52], which may be explored using similar methodologies in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, alternative illumination schemes other than the Gaussian beams modeled within this study have also been reported in the literature (structured illumination, Bessel and Airy beams, multi-photon, etc.) [49][50][51][52], which may be explored using similar methodologies in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Once, it was shown that they are "selfreconstructing" [12] and show enhanced penetration into scattering media [13], they are increasingly investigated in microscopy [14]. Currently, they are explored for their application in neurosciences for opto-genetic stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…39 To exploit the detector's full dynamic range, line confocal detection coupled with scanning illumination has been proposed. 40,41 In the scheme described by Fahrbach and Rohrbach, confocal detection is achieved by exposing the camera at each position of the excitation line and subsequently retaining only the pixel line confocal to the excitation beam. 40 Although this confocal approach allows a signi¯cant enhancement of image contrast, the camera needs to be exposed and readout at each beam position to produce a single¯nal image of the whole¯eld of view, and background rejection is achieved by post-processing the acquired data.…”
Section: Whole-brain High-resolution Neuroanatomymentioning
confidence: 99%